THE ROLE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Hayat KASSI (Ziglôbitha)
Abstract: Artificial intelligence is a diverse field that is experiencing an increasing impact on education, offering significant opportunities to personalize the learning process according to individual student needs. This study aims to explore the impact of artificial intelligence on education by analyzing how it improves student outcomes and customizes educational content, as well as enhances self-directed learning and supports teachers in assessing student performance and providing appropriate guidance. The results showed that artificial intelligence enhances interaction and facilitates self-directed learning through smart tools like virtual assistants, but it faces challenges related to data privacy and the ethics of its use, along with exacerbating the digital divide between schools. Integrating artificial intelligence into education also requires a shift in the teacher's role to become more supervisory and guiding. This study provides a comprehensive understanding of the impact of artificial intelligence on education, enabling educational institutions to improve their strategies and effectively and sustainably leverage technology.